2023
DOI: 10.1111/bjh.19074
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulation with romiplostim as a second‐line strategy in primary immune thrombocytopenia: The iROM study

Alexandra Schifferli,
Axel Rüfer,
Alicia Rovo
et al.

Abstract: SummaryThrombopoietin receptor agonists (TPO‐RAs) stimulate platelet production, which might restore immunological tolerance in primary immune thrombocytopenia (ITP). The iROM study investigated romiplostim's immunomodulatory effects. Thirteen patients (median age, 31 years) who previously received first‐line treatment received romiplostim for 22 weeks, followed by monitoring until week 52. In addition to immunological data, secondary end‐points included the sustained remission off‐treatment (SROT) rate at 1 y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 70 publications
(199 reference statements)
0
7
0
Order By: Relevance
“…In their hypothesis, cytokine alterations that occur in ITP crisis could be reversed after treatment with TPO‐RA, that is, an increase in TGFβ, IL‐4 and IL‐10 and a decrease in Il‐2, IL‐17 and IFNγ. However, Lucchini et al 77 observed some contrary results in the ESTIT trial, including a decrease in IL4, IL10 and TNFα in patients who responded to eltrombopag, so as Schifferli et al that reported a decrease of nearly all cytokines except TGF‐β and IL‐35 in the iROM pilot study 88 …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In their hypothesis, cytokine alterations that occur in ITP crisis could be reversed after treatment with TPO‐RA, that is, an increase in TGFβ, IL‐4 and IL‐10 and a decrease in Il‐2, IL‐17 and IFNγ. However, Lucchini et al 77 observed some contrary results in the ESTIT trial, including a decrease in IL4, IL10 and TNFα in patients who responded to eltrombopag, so as Schifferli et al that reported a decrease of nearly all cytokines except TGF‐β and IL‐35 in the iROM pilot study 88 …”
Section: Discussionmentioning
confidence: 99%
“…In 2022, the iROM study enrolled 13 patients to describe the immunological pattern leading to TFR after 22 weeks of romiplostim administration 88 . Patients included were exposed to first‐line treatment only; nine of them were newly diagnosed and four had chronic ITP.…”
Section: Drug‐induced Sustained Remission In Itp In a Clinical Settin...mentioning
confidence: 99%
See 2 more Smart Citations
“…[88][89][90][91][92] Growing evidence suggests that TPO-RAs support or even induce SROT in adult ITP. 88,93 For adults with primary ITP ( 6 months of disease) showing an insufficient response to first-line treatments like corticosteroids and immunoglobulins, a multicenter phase 2 RCT demonstrated treatmentfree remission (platelets >50/nL) in 32% of patients for at least 6 months posttreatment. 94 This led to the FDA approval for extending romiplostim use as first-line treatment in newly diagnosed adult ITP.…”
Section: Immunomodulation By Tpo-ramentioning
confidence: 99%